The analysis of hydroquinone levels in the product of whitening hand and body lotion in online shops, using the UV-Vis spectrophotometry method - Mellynia, Sri Agfa; Lestari, Yulianita Pratiwi Indah; Mi'rajunnisa (Universitas Islam Indonesia, 2025)
Background: Hydroquinone serves as a skin-lightening agent by suppressing melanin production. However, its usage in cosmetic formulations has been prohibited under the Indonesian Food and Drug Authority regulations, as stated in Regulation Number 18 of 2015. Despite this restriction, numerous studies show that various whitening hand and body lotion products commonly contain hydroquinone.Objective: This study aimed to conduct a qualitative and quantitative analysis of hydroquinone in body-whitening hand and body lotion products available through online retail platforms.Method: The methodology employed in this study involved the use of Thin Layer Chromatography (TLC) for qualitative analysis, complemented by UV-Vis spectrophotometry, which had undergone prior validation to serve as a quantitative analytical tool.Results: The qualitative analysis conducted via Thin Layer Chromatography (TLC) identified six positive samples containing hydroquinone, characterized by an Rf value of 0.75. According to the validation results, the method demonstrated a linearity value with a correlation coefficient (r) of 0.9976, a limit of detection (LOD) of 0.3862 g/mL, and a limit of quantification (LOQ) of 1.2872 g/mL. An RSD value of 1.912% showed precision, while accuracy was confirmed through a recovery rate of 96.77%. The validation outcomes suggested that this approach is robust for analyzing hydroquinone in body-whitening hand and body lotion products. The UV-Vis spectrophotometry result showed that samples 1 through 6 had hydroquinone in them at levels of 0.0418, 0.0448, 0.0361, 0.0283, 0.0365, and 0.3193%, respectively.Conclusion: The research conducted revealed that the qualitative analysis using Thin-Layer Chromatography (TLC) yielded six positive samples, indicating the presence of hydroquinone. Furthermore, the quantitative analysis indicated that whitening hand and body lotion products available in online shops contained hydroquinone at concentrations ranging from 0.0283 to 0.3193 g/mL. This finding underscores the continued prevalence of prohibited chemicals in certain cosmetic products.